Relationship between exercising motivation to reaction time in police officers at special operation units Relación entre la motivación para el ejercicio y el tiempo de reacción de los oficiales de policía en las unidades de operaciones especiales Relação entre la motivação para a prática de exercícios e o tempo de reação de policiais civis de unidades de operações especiais - Matias T.S.* (2015)
© 2015, Editorial Ciencias Medicas. All rights reserved.Introduction: evidences suggest that reaction time (RT) performance is associated with psychological aspects such as motivation. RT and motivation plays an important role in the context of police officers and are known to interact during human decision processes. Objetive: to investigate the relationship between motivational regulations for physical exercise and RT in Police Officers at Special Operation Units. Method: 22 civilian police officers participated in this study (34.5 ± 9.1 years) of the state of Santa Catarina, members of the Special Operations Coordinator-COPE. The reaction time was measured with the TRT_S2012 software with tasks TR simple and TR Mental fatigue. Behavioral Regulation in Exercise Questionnaire-2. Data was analyzed with descriptive and inferential statistics. Results: motivation (r= 0.63, p< 0.01) and external regulation (r= 0.82, p< 0.01) were positively correlated to reaction time. Self-determination index was inversely correlated to reaction time (r= -0.63, p< 0.01). Conclusion: motivation and external regulation affect RT response in police officers from special unit. However, increasing self-determination improves RT performance.